Déjame que te cuente: el storytelling en las campañas políticas actuales - Escalante Villar, Juan (2019)
The changes in society’s perception on politics and corruption, and distrustfulness in politicians’ actions, have made necessary for candidates to transform their campaign strategies. Storytelling, a marketing technique focused on narrating a story in order to transmit a simplified message, is one of the most innovative methods for the optimization of democracy, but its use is still limited. In this article the utility of storytelling is explained, as well as the problems politicians have because of their dependence on the opinion voters have of them. Then, the opportunities, responsibilities and dangers that storytelling entails during political campaigns are briefly evaluated. Finally, recommendations for an adequate use of the technique are established.